International Law and Indigenous People : Self-determination, Development, Consent and Co-management - Barrie, George (Comparative and International Law Journal of Southern Africa, 2020)
The principle of self-determination in international law can refer to political aspirations as well as territorial aspirations. Regarding the latter, the maturation of the discourse on self-determination has provided indigenous peoples with control over their own destiny. This has come about due to an evolutionary development of the principle of self-determination in international law. Self-determination has provided an efficient platform for indigenous peoples to claim their rights to their territories. The true spirit of self-determination has manifested itself as respect for their land without which indigenous peoples cannot fully enjoy their economic and cultural identity. The adoption of the UN Declaration on the Rights of Indigenous Peoples is a vivid illustration of such an outcome. The article analyses the extent to which self-determination encompasses territorial rights for indigenous peoples. This analysis illustrates to what extent self-determination has served as a positive force in the quest of indigenous peoples to territorial rights and how their territorial claims have altered the modern approach to the right to self-determination. Under recent developments indigenous peoples have gained access to international law as ‘actors’ gaining greater control over their own future based on the notion of consent between states and indigenous peoples.